1979
DOI: 10.1136/jnnp.42.6.576
|View full text |Cite
|
Sign up to set email alerts
|

Six month evaluation of thiopropazate hydrochloride in tardive dyskinesia.

Abstract: SUMMARY Using a blind evaluation of cinematographic films of patients suffering from tardive dyskinesia we found that thiopropazate hydrochloride in a dosage up to 30 mg daily was effective in reducing the severity of the dyskinesia in most patients. The overall improvement in the group of patients studied was not significant after one or three months of therapy but was significant after six months of treatment. The administration of thiopropazate hydrochloride over a six month period did not appear to aggrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This design may be a better measure of the neuroleptics’ ability to suppress withdrawal dyskinesias than persistent TD. Other studies were either unblinded or did not use appropriate control groups (Roxburgh 1970; Curran 1973; Jus et al 1979; Smith and Kiloh 1979). Of three particularly well-controlled studies, two found significant long-term suppression (Frangos and Christodoulides 1975; Gerlach and Casey 1983), while the third did not (Korsgaard et al 1984).…”
Section: Suppressive Therapies For Tdmentioning
confidence: 99%
“…This design may be a better measure of the neuroleptics’ ability to suppress withdrawal dyskinesias than persistent TD. Other studies were either unblinded or did not use appropriate control groups (Roxburgh 1970; Curran 1973; Jus et al 1979; Smith and Kiloh 1979). Of three particularly well-controlled studies, two found significant long-term suppression (Frangos and Christodoulides 1975; Gerlach and Casey 1983), while the third did not (Korsgaard et al 1984).…”
Section: Suppressive Therapies For Tdmentioning
confidence: 99%
“…Dopamin-Antagonisten Apomorphin in niedriger Dosis (25,222,235) ButYrophenone (32,89,137,142) Clozapin (101,208,246) Oxiperomid (28) Papaverin (43) Phenothiazin-Derivate (158,212,219) Pimozide (41,88) Sulpirid (29) Tiaprid (40,47) Monoamin-entspeichernde Substanzen Reserpin (123) Tetrabenazin (32,142) Katecholaminsynthese-Blocker Alpha-Methyldopa (123) AI~ha-MethYltYrosin (105) Cholinergika Deanol (76,171) Cholin, Lezithin (100,111,162) Physostigmin (63,229) GABAerge Substanzen 7Baclofen (104,154,174) Benzodiazepine (18,115,213) Valproinsäure ( Literatur…”
Section: Therapeutische Strategienmentioning
confidence: 99%